AESTHETICS OF PLAK-PLIENG GRAVESTONE OF LAMURI KINGDOM ACEH: A STUDY ACCORDING TO SUSANNE KNAUTH LANGER'S AESTHETIC CONCEPT - Rosaguna, Rajes Ikhlas; Purba, Mauly; Priyatno, Agus (Universitas Negeri Medan, 2024)
The Lamuri Kingdom in Aceh has relics in the form of gravestones called